Formas de propagação de espécies de uso medicinal popular em cinco municípios do estado do Amazonas - Hidalgo, Ari de F. [UNESP] (International Society Horticultural Science, 2002)
This work was carried out in five counties of Amazon State, Brazil, along the Solimões/Amazonas and Negro Rivers. The objective was to identify the several forms of natural and induced propagation with medicinal plants, natives and exotics. The peoples were interviewed, with visit and recollection of botanical materials to herborization and reproduction. The greatest parts of plants propagate by seeds (65,8 per cent) and cutting (23,5 per cent). It was showed several species that reproduce by other strategies, like bulbs, rhizomes or brotations. The Amazonian species, in general, propagate by seeds, with some exceptions.
Propagation forms of folk medicinal plants species in five counties in Amazon State
Keywords: Amazonas river; Folk medicine; Negro river; Reproduction; Solimões